2016
DOI: 10.3109/10837450.2015.1125923
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral dosage form development and testing of dimethyl trisulfide, as an antidote candidate to combat cyanide intoxication

Abstract: This study focused on the solubility enhancement and the in vivo antidotal efficacy testing of a new potential cyanide (CN) countermeasure, dimethyl trisulfide (DMTS). Various FDA approved cyclodextrins (HPβCD, RMβCD, HPγCD), cosolvents (ethanol, polyethylene glycols, propylene glycol), surfactants (cremophor EL, cremophor RH 40, sodium cholate, sodium deoxycholate, polysorbate 80) and their combinations were applied. Based on the solubility enhancing potential of the tested systems, polysorbate 80 was chosen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…The physiological safety issues observed here were not observed in the mouse model, 14 though they were evident in a previous formulation. 20 In prior work using the current formulation, mice showed, at worst, minor limping that rapidly recovered. To our knowledge, the severity of toxicity observed in the current experiment has not been observed elsewhere using DMTS.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The physiological safety issues observed here were not observed in the mouse model, 14 though they were evident in a previous formulation. 20 In prior work using the current formulation, mice showed, at worst, minor limping that rapidly recovered. To our knowledge, the severity of toxicity observed in the current experiment has not been observed elsewhere using DMTS.…”
Section: Discussionmentioning
confidence: 86%
“…With this formulation, a DMTS dose of 100 mg/mL provided an APR of 3.4 against KCN. The 200 mg/kg DMTS dose was more effective (4.1 APR) but caused some muscle damage, and the authors suggested 100 mg/kg as the optimal antidotal dose . This formulation was also later found to be stable for at least 100 days when stored in fire‐sealed glass ampules, making it a potential candidate to be stockpiled for use in a mass‐casualty incident .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An 80 mg/mL heparin solution was prepared by dissolving 2.00 g of sodium heparin in 25 mL of distilled water. A DMTS stock solution (Poly80-DMTS) at a concentration of 50 mg/mL was prepared by dissolving DMTS in 15% Poly80 aqueous solution described by Kovacs et al [21] and Petrikovics and Kovacs [12]. …”
Section: Methodsmentioning
confidence: 99%
“…Recently the antifungal [5] and larvicidal [6] activities of DMTS have been reported. DMTS has also been shown to have promising properties as a cyanide antidote [7][8][9].…”
Section: Introductionmentioning
confidence: 99%